Keragaman Jenis Mamalia di Kawasan Ekowisata Mangrove Cukunyinyi Kabupaten Pesawaran - Hasibuan, Mhd Muhajir; Sari, Nurika Arum; Dwiputra, Mohammad Ashari; Permana, Rizki Dimas; Rianingsih, Firma; Adirama, Alfian Zamzami; Witjaya, Oka Rani; Zamili, Abdi Oktarian; Nainggolan, Paolo M.; Aryawan, Adi; Purnomo, Ajis; Sudarsono, Bambang; Hamdani, Hamdani; Alfajrin, Achmad Chalid Alif Afif (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Mangrove ecosystems are important coastal ecosystems that provide a variety of functions. Mangrove ecosystems provide a variety of environmental services including absorbing carbon and contributing to climate change mitigation, protecting coastal areas from storms, tsunamis, and erosion. In addition to providing a variety of environmental services, these ecosystems are also habitats for a variety of living organisms, both aquatic and terrestrial, resident and migrant, also nationally and internationally protected species. The benefits provided by mangrove are contrast to the rate of degradation, which has the potential for loss of wildlife habitat and a decrease in biodiversity value, especially mammals. This study was conducted to analyse the value of biodiversity, especially mammals in the Mangrove Ecotourism Area, Pesawaran Regency. This study uses the method of line transects, mist nets, and sound identification. The results of the study recorded 6 species of mammals with a species diversity value (H') of 1.46, richness of 1.60, evenness of 0.72, and species dominance of 0.30. Mammal species diversity inside the ecotourism area is higher than outside the area. Protected mammals are not found in the area.